A Novel Architecture for M-FSK /DS Spread Spectrum Communication System - husien, ali (Anbar Journal of Engineering Sciences, 2024)
The direct sequence (DS) spread spectrum communication technique is widely regarded as one of the most effective methods of mitigating the effects of a repeating jammer in military communications systems. The proposed system coupled DS with multiple frequency shift keying (DS/MFSK). It is comprised of a transmitter and a receiver. Non-coherent demodulation is examined, as are the spreading sequences in question. The effect of AWGN and Rayleigh fading channels on the proposed approach’s bit error rate (BER) is examined. The investigation demonstrates that even with an 8 dB signal-to-noise ratio, superior outcomes can be achieved; this study’s suggested endeavor is to create a novel transceiver system built on the DS/MFSK modular architecture. MFSK modulation prevents multiple-access interference, while DS is typically employed to boost system efficiency across erratic fading. Test results show that reliability on the AWGN channel decreases a little while reliability is greatly enhanced by Rayleigh fading. Moreover, notable improvements in bandwidth efficiency are achieved.